ROCHESTER INSTITUTE OF TECHNOLOGY: ANALYZING STUDENT SUCCESS - Fasse, Richard; Humbert, Joeann; Rappold, Raychel (Online Learning, 2009)
RIT Online Learning courses have an overall course completion rate of 94%. For lower-division courses, the rate is 92%, undergraduate 93%, and graduate 96%. In this case study. we will share additional measurements we have used to monitor student success and describe strategies we have used to promote online discussion as a key component of effective online courses. We will share results from a large survey of our online students that shows the most interactive courses receive the most positive responses from students. The demographics of our online students have shifted to where almost half our online students are campus-based now. We believe our historical emphasis on interaction in our online courses is serving these new online students equally well, which suggests an important opportunity exists to expand online discussion to more campus-based courses.